The Serious Danger of Viral Infections to Health and the Health Care System and the Urgency of Combating Them - Shaydullaevna , Mamatmusaeva Fotima; qizi , Islambaeva Aziza Aybek; qizi, Qodirova Madina Zafar; qizi , Shorikhsieva Sanobar Erkin (American Journal of Bioscience and Clinical Integrity, 2024)
An integrated global health system was created at MIP to protect against known and unknown infectious diseases. The system consists of many formal and informal networks of organizations that serve various stakeholders. These organizations have different goals, working methods, resources, and accountability, and they work at different regional levels such as regional, national, regional, or global. The system also covers public, private and non-governmental sectors. People of all ages often get viral infections. In general, the spectrum of diseases is wide, but young children and people with weakened or insufficient immune systems are more susceptible to severe outcomes. This chapter discusses the viral causes of diseases that are common in intensive care units, such as myocarditis, hepatitis, pneumonitis and meningitis/encephalitis, etc. The article is devoted to the causes, diagnosis and treatment to help readers in the initial examination of patients with severe viral diseases in terms of diagnosis and specific antiviral therapy. Currently, there is no unified system in the world that could help in creating and coordinating these responses. The creation of a multidisciplinary Global Technical Council on Threats Related to Infectious Diseases will significantly reduce unnecessary costs in the global health system, allow resources to be redirected to where they are needed, and reduce the risk of the spread of infectious diseases.